2020
DOI: 10.1002/zaac.202000336
|View full text |Cite
|
Sign up to set email alerts
|

Pb[PtBi6I12] – Infinite Chains of Heavy Atom Clusters

Abstract: Reaction of Bi with Pb, Pt and BiI3 above 330 °C yielded shiny, black, air insensitive crystals of the subiodide Pb[PtBi6I12]. Pb[PtBi6I12] crystallizes in the rhombohedral space group R3 with lattice parameters a = 1585.39(5) pm and c = 1098.77(3) pm at room temperature. The compound consists of cuboctahedral [PtBi6I12]2– clusters and Pb2+ cations in octahedral coordination between trigonal faces of two cuboctahedra, which concatenate them into linear chains. Six weaker Bi···I inter‐cluster bridges per cluste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…From the +II oxidation state for tin follows the formal charge of 2‐ for the cuboctahedral cluster in accordance with previous findings in similar compounds and general bonding considerations [12,13,16] . Sn II [Pt −II Bi II 6 I −I 12 ] is an electron‐precise situation with all valence electrons localized in chemical bonds or lone pairs and the compound should thus be a bulk semiconductor like the isostructural Pb[PtBi 6 I 12 ] [18] …”
Section: Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…From the +II oxidation state for tin follows the formal charge of 2‐ for the cuboctahedral cluster in accordance with previous findings in similar compounds and general bonding considerations [12,13,16] . Sn II [Pt −II Bi II 6 I −I 12 ] is an electron‐precise situation with all valence electrons localized in chemical bonds or lone pairs and the compound should thus be a bulk semiconductor like the isostructural Pb[PtBi 6 I 12 ] [18] …”
Section: Resultssupporting
confidence: 86%
“…Starting from Sn, Pt, Bi and BiI 3 in the molar ratio 1 : 1 : 2 : 4 (i. e. stoichiometric with respect to Sn[PtBi 6 I 12 ]) and using a temperature program that was based on the syntheses of Bi 2 [PtBi 6 I 12 ] 3 [17] and Pb[PtBi 6 I 12 ], [18] agglomerates of small black cubic crystallites and microcrystalline powder were formed. The X‐ray diffraction pattern of the product indicated that a substance had crystallized that resembled the two compounds mentioned above, but had slightly smaller lattice parameters than the lead compound (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations